The Mythical, Political, and Poetic Crossroads: The Ethnographic Writing of Itamar Vieira Junior in Torto Arado (Global Journal of Human-Social Science, 2025)
This article proposes a reflection on the literary writing of Itamar Vieira J nior in the novel Torto Arado 2019 based on the concept of ethnographic writing and articulating contributions from L lia Gonzalez 1984 Clifford Geertz 1989 Walter Benjamin 1994 Antonio Candido 2004 2006 Braun 2012 Nesimi 2019 among other authors The analysis focuses on the construction of a diasporic literary phenomenon in which mythology politics and poetry intersect within a narrative that translates the listening to racialized and territorialized bodies in the Brazilian hinterlands sert o The discussion is guided by the hypothesis that the textual construction represents a subjective-objective process in which the author acts as an ethno translator From this perspective the crossroads is explored as a symbolic and epistemological category and literature as a form of social mediation The crossroads in this sense materializes the entanglement of multiple temporalities identities and knowledge systems present in the narrative reinforcing the author s role as a mediator between the lived experience of sert o communities and their literary representation
Keywords: torto arado; ethno–translation; amefrican crossroads; diasporic literature